2020
DOI: 10.1021/acs.jced.0c00430
|View full text |Cite
|
Sign up to set email alerts
|

Diffusivities in Binary Mixtures of [AMIM][NTf2] Ionic Liquids with the Dissolved Gases H2, He, N2, CO, CO2, or Kr Close to Infinite Dilution

Abstract: Ionic liquids (ILs) are interesting working fluids in many areas of chemical and energy engineering such as gas separation, catalysis, or energy storage. For the optimum design of related processes and apparatuses, the diffusion coefficient of gases dissolved in ILs is necessary, yet is often only known for a few selected gases. In this work, the thermal and mutual diffusivities in binary mixtures consisting of the gases hydrogen, helium, nitrogen, carbon monoxide, carbon dioxide, or krypton dissolved in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(65 citation statements)
references
References 103 publications
7
58
0
Order By: Relevance
“…The present work provides a link to previous investigations ,,,, studying the Fick diffusion coefficient D 11 as well as the structure–property relationships in the liquid phase of binary mixtures consisting of a liquid and a dissolved gas close to infinite dilution. As solvents, nonpolar n -alkanes, polar 1-alcohols, or bis­(trifluoromethylsulfonyl)­imide ([NTf 2 ] − )-based ionic liquids (ILs) with varying carbon chain lengths were investigated.…”
Section: Introductionmentioning
confidence: 55%
See 4 more Smart Citations
“…The present work provides a link to previous investigations ,,,, studying the Fick diffusion coefficient D 11 as well as the structure–property relationships in the liquid phase of binary mixtures consisting of a liquid and a dissolved gas close to infinite dilution. As solvents, nonpolar n -alkanes, polar 1-alcohols, or bis­(trifluoromethylsulfonyl)­imide ([NTf 2 ] − )-based ionic liquids (ILs) with varying carbon chain lengths were investigated.…”
Section: Introductionmentioning
confidence: 55%
“…The results for the n -alkane- and 1-alcohol-based systems obtained in the previous work served for the development of a semiempirical model for the prediction of D 11 . , This model requires only pure-component properties of the solute and solvent and was able to predict D 11 of the studied systems and a set of similar systems from the literature with a typical deviation of 10% . The studies regarding the [NTf 2 ] − -based ILs have furthermore shown that in such highly viscous systems, D 11 is nearly independent of the viscosity of the IL solvents at a given temperature . Aiming to study the influence of the larger molar weight and dipole moment of the solutes on D 11 close to infinite dilution, investigations in the present study are extended to binary mixtures consisting of n -hexane (C 6 H 14 ) or 1-hexanol (C 6 H 14 O) with the dissolved gases methane (CH 4 ), neon (Ne), Kr, 1,1,1-trifluoroethane (R143a), sulfur hexafluoride (SF 6 ), or 1,1,1,3,3,3-hexafluoropropane (R236fa).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations